ENT300: Fundamentals of Entrepreneurship QAHWAH CAFE / Nur-Asikin Abdul Rahman... [et al.] - Abdul Rahman, Nur-Asikin; Yusuf, Afiqah Humaira; Awang Jidel, Dayangku Nurdayana; Halik, Suhana; Raduan, Nurul Mida (2015)
QAHWAH CAFE is a coffee cafe located at that allows students from the nearby university which is Kolej Laila Taib and UCTS. Other than that, our company can allows many other people instead of students such as businessman and other people that stay at that area. QAHWAIA CAFE also serves different service such as type of coffee that will serve compare to the other coffee shop. Besides that, we are providing meeting room and discussion room that will give students or businessman some comfortable places to make any discussion among them. Other than that, people who will across from the city to the college or to the nearby village can decide to layover to our cafe.